How Not to Make A Megacity. - Goldstein, H.
Despite Nigeria's enormous oil wealth, tens of billions of dollars have gone missing over the years in this country - one of the world's most corrupt - and few investments have been made in infrastructure. This paper presents environmental, health, political and energy problems the Lagos city of Nigeria is currently experiencing.
Keywords: Lagos city; Nigeria; Energy problems; Environmental problems; Health problems; Infrastructure; Political problems